A Recombinant Potato virus Y Infectious Clone Tagged with the Rosea1 Visual Marker (PVY-Ros1) Facilitates the Analysis of Viral Infectivity and Allows the Production of Large Amounts of Anthocyanins in Plants - Cordero, Teresa; Mohamed, Mohamed A.; López-Moya, Juan-José; Daròs, José-Antonio (Frontiers in Microbiology, 2017)
Potato virus Y (PVY) is a major threat to the cultivation of potato and other solanaceous plants. By inserting a cDNA coding for the Antirrhinum majus Rosea1 transcription factor into a PVY infectious clone, we created a biotechnological tool (PVY-Ros1) that allows infection by this relevant plant virus to be tracked by the naked eye with no need for complex instrumentation. Rosea1 is an MYB-type transcription factor whose expression activates the biosynthesis of anthocyanin pigments in a dose-specific and cell-autonomous manner. Our experiments showed that the mechanical inoculation of solanaceous plants with PVY-Ros1 induced the formation of red infection foci in inoculated tissue and solid dark red pigmentation in systemically infected tissue, which allows disease progression to be easily monitored. By using silver nanoparticles, a nanomaterial with exciting antimicrobial properties, we proved the benefits of PVY-Ros1 to analyze novel antiviral treatments in plants. PVY-Ros1 was also helpful for visually monitoring the virus transmission process by an aphid vector. Most importantly, the anthocyanin analysis of infected tobacco tissues demonstrated that PVY-Ros1 is an excellent biotechnological tool for molecular farming because it induces the accumulation of larger amounts of anthocyanins, antioxidant compounds of nutritional, pharmaceutical and industrial interest, than those that naturally accumulate in some fruits and vegetables well known for their high anthocyanin content. Hence these results support the notion that the virus-mediated expression of regulatory factors and enzymes in plants facilitates easy quick plant metabolism engineering.